2003
DOI: 10.1096/fj.02-0640fje
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C9‐derived epoxyeicosatrienoic acids induce angiogenesis via cross‐talk with the epidermal growth factor receptor

Abstract: Cytochrome P450 (CYP) epoxygenase products, such as 11,12-epoxyeicosatrienoic acid (EET), stimulate endothelial cell proliferation. We set out to identify the signal transduction cascade linking EET generation to enhanced proliferation and angiogenesis. In human endothelial cells overexpressing CYP 2C9, cell number was increased compared with control cells and was inhibited by the CYP 2C9 inhibitor, sulfaphenazole. CYP 2C9 overexpression was associated with the activation of Akt and an increase in cyclin D1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
182
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 157 publications
(186 citation statements)
references
References 55 publications
3
182
1
Order By: Relevance
“…The degree of angiogenesis is not yet routinely evaluated in the clinical setting in Sweden, and we could, therefore, not evaluate whether there was any association between peritumoral vascular invasion and CYP2C8/9 haplotypes. It is plausible that we could have found an association, since CYP2C9-derived EETs stimulate angiogenesis (Michaelis et al, 2003). CYP2C9-derived EETs do so by a mechanism involving activation of the EGFR (Michaelis et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The degree of angiogenesis is not yet routinely evaluated in the clinical setting in Sweden, and we could, therefore, not evaluate whether there was any association between peritumoral vascular invasion and CYP2C8/9 haplotypes. It is plausible that we could have found an association, since CYP2C9-derived EETs stimulate angiogenesis (Michaelis et al, 2003). CYP2C9-derived EETs do so by a mechanism involving activation of the EGFR (Michaelis et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…It is plausible that we could have found an association, since CYP2C9-derived EETs stimulate angiogenesis (Michaelis et al, 2003). CYP2C9-derived EETs do so by a mechanism involving activation of the EGFR (Michaelis et al, 2003). One study reported high expression of EGFR to be inversely correlated with nodal metastases and shorter, distant disease-free survival in a group of breast cancer patients who had received 2 years of adjuvant tamoxifen treatment (Dihge et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 A), and although the EETs reported to induce angiogenesis in the chick chorioallantoic membrane (Michaelis et al, 2003) and the vascularization of Matrigel plugs implanted into wild-type mice Webler et al, 2008). Moreover, the overexpression of the human CYP2C11 and 2J2 enzymes in the ischemic rat hindlimb model was found to increase muscle capillary density (Wang et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…The first link between CYP enzymes and angiogenesis was obtained in co-cultures of astrocytes and endothelial cells in which arachidonic acid epoxides (epoxyeicosatrienoic acids [EETs]) released from astrocytes increased endothelial cell proliferation and elicited the formation of capillary-like structures (Munzenmaier and Harder, 2000;Zhang and Harder, 2002). Also, the overexpression of the CYP2C9 epoxygenase in, and/or the application of 11,12-or 14,15-EET to monocultures of endothelial cells was associated with angiogenesis Michaelis et al, 2003). In vivo data rapidly followed to support these in vitro findings, with corresponding diols by the soluble epoxide hydrolase (sEH; gene = Ephx2; Konkel and Schunck, 2011;Imig, 2012).…”
mentioning
confidence: 99%